Breastfeeding duration and residential isolation amid Aboriginal children in Western Australia - Cromie, E.; Shepherd, Carrington; Zubrick, S.; Oddy, W. (MDPI Publishing, 2012)
Objectives: To examine factors that impact on breastfeeding duration among Western Australian Aboriginal children. We hypothesised that Aboriginal children living in remote locations in Western Australia were breastfed for longer than those living in metropolitan locations. Methods: A population-based cross-sectional survey was conducted from 2000 to 2002 in urban, rural and remote settings across Western Australia. Cross-tabulations and multivariate logistic regression analyses were performed, using survey weights to produce unbiased estimates for the population of Aboriginal children. Data on demographic, maternal and infant characteristics were collected from 3932 Aboriginal birth mothers about their children aged 0–17 years (representing 22,100 Aboriginal children in Western Australia). Results: 71% of Aboriginal children were breastfed for three months or more. Accounting for other factors, there was a strong gradient for breastfeeding duration by remoteness, with Aboriginal children living in areas of moderate isolation being 3.2 times more likely to be breastfed for three months or more (p <0.001) compared to children in metropolitan Perth. Those in areas of extreme isolation were 8.6 times more likely to be breastfed for three months or longer (p <0.001). Conclusions: Greater residential isolation a protective factor linked to longer breastfeeding duration for Aboriginal children in our West Australian cohort.